1989
DOI: 10.1007/bf00910773
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in school-aged children with pervasive attention deficit hyperactivity disorder

Abstract: This study investigated 54 children (37 boys and 17 girls) with cross-situational attention deficit hyperactivity disorder (ADHD) to determine whether there are sex differences in the expression of either the primary or secondary symptomatology of ADHD. Results indicated that the male and female ADHD groups were strikingly similar on all measures of primary (impulsivity, inattention, and overactivity) and secondary (learning problems, externalizing symptoms, internalizing symptoms, peer relationship difficulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 30 publications
5
67
0
Order By: Relevance
“…This result is consistent with several previous studies that found no differences on cognitive measures between boys and girls with ADHD (Breen, 1989;Horn, Wagner, & Ialongo, 1989), but some studies suggest that girls with ADHD have lower intelligence scores and more learning problems than boys with ADHD (Brown, Madan-Swain, & Baldwin, 1991;Gaub & Carlson, 1997;James & Taylor, 1990). The examination of sex differences in the cognitive and academic profiles of girls and boys with ADHD is an area that has important implications for identification and treatment and will require further cross-sectional and longitudinal study to reconcile these discrepant findings from studies that used different age groups and ascertainment strategies.…”
Section: Discussionsupporting
confidence: 83%
“…This result is consistent with several previous studies that found no differences on cognitive measures between boys and girls with ADHD (Breen, 1989;Horn, Wagner, & Ialongo, 1989), but some studies suggest that girls with ADHD have lower intelligence scores and more learning problems than boys with ADHD (Brown, Madan-Swain, & Baldwin, 1991;Gaub & Carlson, 1997;James & Taylor, 1990). The examination of sex differences in the cognitive and academic profiles of girls and boys with ADHD is an area that has important implications for identification and treatment and will require further cross-sectional and longitudinal study to reconcile these discrepant findings from studies that used different age groups and ascertainment strategies.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the defiant behavior is not manifested through an isolated circumstance but pervasive across different situations. This approach is consistent with that of Horn, Wagner, and Ialongo (1989) favoring the diagnostic import of pervasive behavior and with the view that behavior emergent only in isolated situations is far more likely to be random or reactive than pathognomonic.…”
supporting
confidence: 71%
“…The present results suggest, further, that girls may not be identified as often as boys because they perform better on objective measures of attention. Studies of children referred for AD/HD either report no gender differences in attention (Breen, 1989;Brown et al, 1991;Horn, Wagner, & Ialongo, 1989) or find more cognitive and learning problems in the girls (Berry et al, 1985;James & Taylor, 1990). Given that girls generally perform better on attention tests, it is possible that we are diagnosing with AD/HD only those girls with severe difficulties, and that, moreover, more girls may benefit from treatment than are currently being treated.…”
Section: Implications For Clinical Practicementioning
confidence: 99%